Carbon nanocomposite electrodes for electrical double layer capacitor. (December 2020) - Daraghmeh, Allan; Hussain, Shahzad; Haq, Atta Ul; Saadeddin, Iyad; Servera, Llorenç; Ruiz, JM
Abstract: Activated carbons (ACs) have been used as electrode material in commercial electric double-layer capacitors (EDLC) due to their low cost, high specific surface area, and chemical stability. Unfortunately, the supercapacitive performance of AC is not satisfactory due to their low conductivity.On the other hand, carbon nanofibers (CNFs) based EDLC exhibit low equivalent series resistance ( ESR ) but not such energy storage values as AC ones. Here in this paper, we report on the synthesis of new nanocomposites based on a mixture of ACs and CNFs using a simple powder processing route and evaluating their electrochemical behavior as electrode materials in symmetric EDLC. The EDLC, with 10 wt. % CNFs in AC/CNFs as the electrodes have displayed a high conductivity and surface area resulting in the enhancement of the energy and power delivers in aqueous electrolyte. On the contrary, with 90 wt.% CNFs in AC/CNFs as the electrodes, higher specific power, low ESR, and low value of relaxation time constant are achieved. The highest value of specific capacitance estimated is around 207 F g −1 at 5 mV s −1 and the highest specific energy is 13.2 Wh kg −1 at 1 A g −1 for the 10 wt.% CNFs in AC/CNFs. Graphical abstract: Image, graphical abstract